2023
DOI: 10.1101/2023.06.28.546848
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapy-associated remodeling of pancreatic cancer revealed by single-cell spatial transcriptomics and optimal transport analysis

Abstract: In combination with cell intrinsic properties, interactions in the tumor microenvironment modulate therapeutic response. We leveraged high-plex single-cell spatial transcriptomics to dissect the remodeling of multicellular neighborhoods and cell-cell interactions in human pancreatic cancer associated with specific malignant subtypes and neoadjuvant chemotherapy/radiotherapy. We developed Spatially Constrained Optimal Transport Interaction Analysis (SCOTIA), an optimal transport model with a cost function that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Altogether, this string of insights provides a potential mechanistic foundation for several recent studies that showed a high degree of heterogeneity in the neoplastic and stromal immune compartments in human PDAC, including hybrid/intermediate/co-expressor CLA/BL subtype states that exist in naive and therapy-treated PDAC tumors 1016,20,36,37 . We propose that extrinsic regional TNF-α plays an essential role in destabilizing CLA neoplastic cell identity by promoting BL cJUN/AP1-mediated transcriptional programs.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Altogether, this string of insights provides a potential mechanistic foundation for several recent studies that showed a high degree of heterogeneity in the neoplastic and stromal immune compartments in human PDAC, including hybrid/intermediate/co-expressor CLA/BL subtype states that exist in naive and therapy-treated PDAC tumors 1016,20,36,37 . We propose that extrinsic regional TNF-α plays an essential role in destabilizing CLA neoplastic cell identity by promoting BL cJUN/AP1-mediated transcriptional programs.…”
Section: Discussionmentioning
confidence: 82%
“…Complementarily, we here show that JUNB/AP1 acts as a counterpart to promote a favorable CLA phenotypic identity in PDAC. Of note, JUNB/AP1-mediated transcriptional programs can also confer tumor-promoting functions in other cancer types [39][40][41] ; JUN/AP1 TFs are highly context dependent and may co-operate for target gene transcription [41][42][43] or oppose one another 44 Altogether, this string of insights provides a potential mechanistic foundation for several recent studies that showed a high degree of heterogeneity in the neoplastic and stromal immune compartments in human PDAC, including hybrid/intermediate/coexpressor CLA/BL subtype states that exist in naive and therapy-treated PDAC tumors [10][11][12][13][14][15][16]20,36,37 . We propose that extrinsic regional TNF-α plays an essential role in destabilizing CLA neoplastic cell identity by promoting BL cJUN/AP1-mediated transcriptional programs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Single-cell RNA sequencing (scRNA-seq) is a valuable tool for characterizing TME as it provides insights into cellular heterogeneity and molecular subtypes (17,18). Several scRNA-seq studies have explored the PDAC TME, offering valuable insights into this complex ecosystem (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). However, scRNA-seq techniques lack spatial context, and are susceptible to cell dissociation-associated artifacts.…”
Section: Introductionmentioning
confidence: 99%